Architecto moderno na cidade: traços e rastros de Luiz Olivieri em Belo Horizonte - Rita Lages Rodrigues (2012)
Luiz Olivieri came to Belo Horizonte in l895, where he stayed until 1937, the year of his death, as a member of Comissao Construtora da Nova Capital. Graduated in Florence, he worked at Belo Horizonte as an architect, his main professional activity, as well as a designer, sculptor and painter. Traces of his presence remained in central places of the city, his architectural masterpieces are still in key positions. His production is not limited to architectural works, materialized in stone and other materials in the city. There are sculptures of his own in Museu Historico Abilio Barreto, as well as postcards that belonged to him and other objects. There are also copies of the first and second edition of the book O Architecto no Brasil, written by him. In addition to these objects, there are designs of his own that are approved for construction in the city. The existence of his productions in the city was essential to the central problem of the thesis: the analysis of the mark of an inhabitant of the town that, within a certain range of possibilities, acted and contributed to the configuration of Belo Horizonte urban space in its early decades. To approach the individual and the city, a micro historical biography was written considering the relation between the past, the present and the future, at the time of the architect's life and also at the time that his works became heritage of Belo Horizonte. The sensitive shared by Olivieri at the time of its existence, and by the men who later shared the need for permanence of his works in the urban space, shows us that Olivieri left marks in the city that represents a time. We tried to think over the historian work through the existing remains, writing a text about a man in a biographical space. We considered the dual temporal dimension: the making of the historian and the resident of the town that thinks and acts in its temporal existence: between expectation and experience, men act in many ongoing presents. The approach of Olivieris life served as background to this debate and also to understand the existence of an architect in their social networks, in the first decades of the capital.